Empowerment Of Family Welfare (PKK) In Gender-Based Families Economic Empowerment In Rao District - Ghea Edsanty; Jalius Jalius (Universitas Negeri Padang, 2022)
This research is motivated by the success of the community in Rao District in making sinhok fish into processed sinhok fish chips so that this skill can support the family economy and improve the community's economy. The aim of this research is to describe the role of empowering family welfare in gender-based family economic empowerment which is seen from the aspect of capital assistance, aspects of infrastructure development assistance, and aspects of mentoring assistance.The research approach is qualitative while the type is a case study. Sources of data used are women in Rao sub-district as research subjects and instructors and local residents as research informants. Data collection techniques used are interviews, observation and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Source triangulation is used as a data validity technique.The results of this study indicate that the empowerment of family welfare skills in processing Sinhok fish into Sinhok fish chips is very good, this can be noted from: (1) Aspects of capital assistance, the results show that gender-based family welfare empowerment of Sinhok fish processing into Sinhok fish chips is seen to increase knowledge the community about processing sinhok fish into delicious preparations. (2) Aspects of infrastructure development assistance obtained results that the processing of Sinhok fish already has the support of good facilities and infrastructure. (3) Aspects of assistance assistance obtained from gender-based family empowerment in processing sinhok fish into sinhok fish chips can be seen from the assistance and monitoring carried out by PKK members who are tasked with accommodating and facilitating the smooth production of sinhok fish chips.Keywords: Elderly Empowerment, Processing of Sinhok Fish Chips, Rao District